CTNI-11. TUMOR-TREATING FIELDS COMBINED WITH SECOND-LINE CHEMOTHERAPY IN RECURRENT GLIOBLASTOMA: A MATCHED RETROSPECTIVE STUDY. (12th November 2021) - Mou, Yonggao; Qun-ying, Yang; Guo, Cheng-Cheng; Deng, Meiling; Chen, Yin-Sheng; Du, Xiao-Jing; Wu, Shao-xiong; Wang, Jian; Ke, Sai
Abstract: OBJECTIVE: Tumor-treating Fields (TTFields) has been approved for patients with newly diagnosed and recurrent GBM. However, TTFields combined with second-line chemotherapy has not been well studied in china. This study aims to explore the efficacy and safety of such combination therapy for recurrent GBM. METHODS: Forty-nine patients with supratentorial GBM who failed the standard Stupp treatment from April 2019 to January 2021 in our center were enrolled. Fourteen patients received combination therapy while 35 received second-line chemotherapy alone (temozolomide or CPT-11) as a control. PFS, OS, and adverse reactions were compared. RESULTS: There were no significant differences between these two groups in baseline characteristics except the use of anti-angiogenesis drugs which was higher in the control group. The median duration of TTFields was 19 weeks (10.1-43.4) with a median compliance rate of 93.5% (67-97%). The control group had a higher rate of disease progression than the combination group (adjusted HR=2.49, 95% CI: 1.08-5.75, P=0.033). The 6-month PFS rate was 55.6% (95% CI: 26.6%-77.0%) in the combination group, and 29.2% (95% CI：14.9%-45.1%) in the control group (p=0.03). The median OS was 8.6 months (95% CI: 3.9-NE) and 7.1 months (95% CI:5.1-9.8), respectively (HR=1.29, P= 0.56). Skin rash beneath the tranducer arrays was a common adverse event in the combination group (42.6% mild and 14.3% moderate). This condition was easily treated with topical corticosteroids and did not require substantial treatment breaks. CONCLUSION: TTFields combined with second-line chemotherapy had significantly less progression rate than chemotherapy alone for patients with recurrent GBM. In addition, the combination therapy was well tolerated.